Researc of pro- and anti-inflammatory cytokines dynamic on the background of endothelial dysfunction development induced by experimental osteoarthrosis - Savytskyi, I. V.; Orel, K. S.; Miastkivska, I. V.; Savytskyi, V. I.; Levkivska, O. S. (Journal of Education, Health and Sport, 2018)
Study have been carried out on white Wistar line rats (age – 3 months, weight – 180-220 g). According to the tasks the animals were divided into 7 groups: 1st group is intact (n = 20). 2nd group is rats, which were modeled osteoarthritis without further correction and were withdrawn from the experiment in the first stage (7th day) (n=40). 3rd group is rats, which were modeled osteoarthritis without further correction and removed from the experiment in the second stage (21st day) (n=40). 4th group is rats, in which experimental osteoarthritis was corrected with nonsteroidal anti-inflammatory drugs (NSAIDs) (Diclofenac) and aminoguanidine and removed from the experiment in the first stage (7th day) (n=20). 5th group is rats, in which experimental osteoarthritis was corrected with NSAIDs (Diclofenac) and aminoguanidine and withdrawn from the experiment in the second stage (21st day) (n=20). 6th group is rats, where experimental osteoarthritis was corrected using NSAIDs and a 7% L-arginine solution and withdrawn from the experiment in the first stage (7th day) (n=20). 7th group is rats, in which experimental osteoarthritis was corrected with NSAIDs and 7% L-arginine solution and withdrawn from the experiment in the second stage (21st day) (n=20). Animals were withdrawn from the experiment for the 7th day and the 21st day after the simulation of the pathological condition. NSAIDs (Diclofenac), aminoguanidine and L-arginine were administered from the beginning of the study. It were found during the experiment, increased levels of Interleukin 1β and Interleukin 10 in the simulated osteoarthrosis pathogenesis. It has been established positive dynamics of these cytokines in the endothelial dysfunction correction at osteoarthritis with the aminoguadine correction. It was revealed more pronounced efficacy of using L-arginine as a corrective means of impaired endothelial function in experimental osteoarthritis. Comparative characteristics of correction agents has shown that the use of nitric oxide donor is more effective than incubation of inducible NO synthase. It was proved normalization of endothelial functional status indicators in the group of animals treated with L-arginine as a part of complex correction of osteoarthrosis was proved.